Oxytocin moderates risky decision-making during the Iowa Gambling Task: A new insight based on the role of oxytocin receptor gene polymorphisms and interventional cognitive study. (24th August 2019) - Bozorgmehr, Ali; Alizadeh, Fatemeh; Sadeghi, Bahman; Shahbazi, Ali; Norouzi Ofogh, Sattar; Joghataei, Mohammad Taghi; Razian, Shima; Heydari, Fahimeh; Ghadirivasfi, Mohammad
Highlights: Genetic association study showed a link between OXTR gene and risky decision-making. Intranasal oxytocin and TT genotype increased net score in Iowa Gambling Task. Intranasal oxytocin and TT genotype did not change total time in Iowa Gambling Task. Intranasal oxytocin and TT genotype lowered risky decisions compared to CT and CC. rs2254295 and T allele may modulate the function of OXTR gene in decision-making. Abstract: The oxytocinergic system influences attentional bias towards emotional cues and feedback-based learning. Considering a tag single-nucleotide polymorphism (SNP) found through analysis of an intronic haplotype in the oxytocin receptor (OXTR) gene, we investigated the effect of oxytocin on risky decision-making via the Iowa Gambling Task (IGT). Young healthy males received intranasal oxytocin or placebo, and the IGT was performed where raw scores, net scores and total time were recorded, and ratio of advantageous to disadvantageous choices was calculated. Using PCR-pyrosequencing, a 761 bp target sequence in the OXTR gene was amplified and sequenced after the extraction of whole blood DNA. Employing Haploview, haplotypes and linkage disequilibrium (LD) pattern among all 14 SNPs in the intronic region were determined based on D′ and LOD values, and rs2254295 with the highest LD was indicated as the tag SNP. GTT was shown to have the highest frequency among the found haplotypes. Oxytocin group and participants with the TT genotype demonstrated a significantly increased raw score, net score and advantageous choices, whereas the total time was not influenced remarkably. This means that oxytocin significantly reduced the risk taking in decision-making, and participants with the TT genotype had less premature or risky decisions than those with the CT and CC genotypes. rs2254295 may modulate the function or expression of the OXTR gene, implying that T allele may increase the expression of the OXTR gene compared to C allele. We suggest that oxytocin may remarkably moderate the risk attitude and its consequences during uncertain decision-making.